Thermochemical Heat Storage Properties of Co3O4-X wt % Al2O3 and Co3O4-X wt % Y2O3 Composites (X=1, 2, 5, 8, 10) - Azin Hasanvand; Mehdi Pourabdoli; Ahmad Ghaderi Hamidi (Journal of Renewable Energy and Environment, 2019)
The effect of Al2O3 (1-10 wt %) and Y2O3 (1-10 wt %) additions on thermochemical heat storage properties of Co3O4/CoO system was investigated by thermogravimetry, XRD, and SEM analyses. Results showed that the addition of Al2O3 to Co3O4 at constant 8 h mechanical activation improved the redox cycle stability and increased oxygen sorption value and rate. It was found that oxygen sorption and their rate decreased with increasing the alumina content to more than 8 wt %. The formation of the spinel phase and an increase in its amount by increasing the alumina content led to a decrease in the oxygen sorption capacity. SEM studies showed that Al2O3 prevented the sintering and particle growth of cobalt oxide particles during reduction and re-oxidation processes. In addition, results showed that the addition of Y2O3 in all ranges to Co3O4 improved the redox cycle stability of cobalt oxide; however, it significantly decreased the oxygen sorption in the Co3O4/CoO system. XRD patterns of a sample containing 10 wt % yttria before the redox process indicated the presence of only Co3O4 phase; however, after three redox cycles, other phases including CoO and Y2O3 appeared.